Sarkasme Politik dalam Perspektif Hak Asasi Manusia - Aly Ubaid Arafi'i; Kun Budianto; Siti Anisyah (Prodi Ilmu Politik FISIP Universitas Islam Negeri Raden Fatah Palembang, 2023)
ABSTRACK This research is entitled Political Sarcasm Against President Joko Widodo Period 2019 – 2024 on Twitter in a Human Rights Perspective. Freedom of expression is placed as a form of freedom in seeking information and then discussing whether to support or criticize it as a process to remove our misconceptions about facts and values. The use of sarcasm is considered as one of freedom of expression. In fact, the use of sarcasm on Twitter in criticizing Joko Widodo's government resulted in intervention and even imprisonment. This study aims to find out how political sarcasm is used against President Joko Widodo for the 2019 – 2024 period on Twitter from a human rights perspective. The theory used is the theory of freedom of expression according to Joel Feinberg which in his view states that there are limits to freedom of expression. The results of this study discuss tweets from various accounts on Twitter that wrote and uploaded sarcasm towards President Joko Widodo in the 2019-2024 period. . The use of sarcasm was in an effort to criticize President Joko Widodo. There are sarcasm that are harsh and unpleasant to hear so that there are expressions of sarcasm on Twitter which end up in court because the tweets cause insults to individuals and religious groups. The use of sarcasm can be trapped by violations of the Articles of the ITE Law and can go beyond the limits of freedom of expression according to Joel Feinberg.